Clinical and demographic profile of peripheral neuropathy in chronic kidney disease in tertiary hospital in Bundelkhand region, Central India - Sengar NS; Arvind Kankane; Shailja Singh; Nutan Agrawal (Asian Journal of Medical Sciences, 2023)
Background: Peripheral neuropathy is the most common chronic kidney disease (CKD)-related complication, with a prevalence of more than 60%. It is directly proportional to the duration and severity of CKD. Aims and Objectives: The study focuses on the prevalence, clinical, and demographic profile of peripheral neuropathy in CKD patients. Materials and Methods: The present study was cross-sectional and conducted in a tertiary hospital in Central India from October 2021 to September 2022. Among 100 CKD patients, peripheral neuropathy was assessed clinically and by electrophysiological nerve conduction studies. Results: Out of 100 subjects, 66% were male and 34% were female. Males were affected more (66.66%) than females (58.82%). Out of 46 pre-hemodialysis (HD) patients, 25 (54.34%) showed peripheral neuropathy. Out of 54 HD patients, 41 (75.92%) showed peripheral neuropathy, maximum age group with neuropathy >60 years, duration of uremia of 31–36 months, and average creatinine >9 mg/dL. The most common pattern observed was mixed sensory-motor neuropathy (axonal+demyelination) at 86.36%. Conclusion: The prevalence of peripheral neuropathy increases with the duration and severity of CKD. The most common pattern is distal symmetrical mixed sensory-motor neuropathy.